Chronic non-puerperal uterine inversion - Muhammad, Zakari; Ibrahim, Saidu; Yakasai, Ibrahim (Nigerian Journal of Basic and Clinical Sciences, 2026)
Inversion of the uterus is a rare clinical problem. Non-puerperal inversion usually results from a tumor arising from the fundus of the uterus. We report two cases of chronic non-puerperal uterine inversion in a 38-year-old and a 54-year-old postmenopausal woman. They both presented with vaginal bleeding, a mass protruding from the vagina and lower abdominal pain. Diagnosis was made based on these clinical features. At first, vaginal myomectomy was performed and after that, a Kustner procedure and vaginal hysterectomy was performed in both cases. Early diagnosis and appropriate surgical treatment of the inverted uterus are important to prevent further complications.